INCLUSIVE EDUCATION PRACTICES: INTEGRATING MOTOR ACTIVITY FOR DIVERSE LEARNERS - Giovanni , R. Bianchi; Laura , M. Rossi (Research Journal of Education and Allied Studies, 2024)
Carrying out motor and sporting activities for a disabled person, or one who is physically, economically or socially disadvantaged, is the exaltation of his or her abilities, even if they are residual, and of what he or she can do, in a world that always reminds him or her of what he or she is unable to be and what he or she lacks. This paper analyses how the initiation into motor and/or sports practice of individuals with intellectual and/or mental, relational or social criticalities, aims to promote their inclusion, self-esteem, social integration and prevent the risk of onset of chronic degenerative diseases and improve their quality of life.